An Analysis Upon Nutritional Requirement and Status of Pre-School Children: a Case Study of Purulia District In West Bengal: Examining the nutritional status and requirements of pre-school children in Purulia District, West Bengal (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Nutrition and health were the most important contributory factors forhuman resource development in the country (Amirthaveni and borikor, 2001). Butstill, undernourishment continued to be a major public health issue and causedof a substantive proportion of all child deaths in every years specifically indeveloping countries like India (black et al., 2003). The large sections ofIndian publication were suffered from varying of energy deficiency. The most vulnerable group regarding health and nutritional status waspreschool children living in rural as well as in urban slum areas, within thetribal preschool children were the main victims of under nourishment. The past seven decades have seen remarkableshifts in the nutritional scenario in India. Even up to the 1950s severe formsof malnutrition such as kwashiorkar and pellagra were endemic. As nutritionistswere finding home-grown and common-sense solutions for these widespreadproblems, the population was burgeoning and food was scarce. The threat ofwidespread household food insecurity and chronic under nutrition was very real.Then came the Green Revolution. Shortages of food grains disappeared withinless than a decade and India became self-sufficient in food grain production. India has variety of tribal population they constitute about 8% oftotal population, these are considered to be aboriginals and confined to livingin hilly and dense forest area isolated from the main stream. A great majorityof them inhabitant in the central India.